EFFICIENCY OF POLITICAL BUDGET USE IN ELECTORAL CAMPAIGNS: A REVIEW OF THE LITERATURE - Melyana R Pugu; Al-Amin (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This research presents a literature review on budget efficiency in political campaigns, particularly in the context of electoral campaigns. The research aims to identify elements and best practices that can improve political campaign budget efficiency. The literature reviewed shows that careful planning, technology utilisation, community engagement and transparency practices play an important role in effective budget management. Strategic planning enables appropriate resource allocation, while technology provides cost-effective solutions to reach voters. In addition, collaboration with various stakeholders and the use of volunteers can significantly reduce expenditure. Transparency and accountability in budget management are also key factors that can increase public trust in candidates and political parties. This research concludes that budget efficiency in political campaigns is not only related to cost savings, but also an indicator of prudent and ethical management, which ultimately contributes to the success of the campaign and increases public trust.